Sex-specific prevalence, inequality and associated predictors of hypertension, diabetes, and comorbidity among Bangladeshi adults: results from a nationwide cross-sectional demographic and health survey - Abdur Razzaque Sarker; Raisul Akram; Nausad Ali; Marufa Sultana; Nurnabi Sheikh (BMJ Open)
Objectives To determine the sex-specific prevalence, inequality and factors associated with healthcare utilisation for diabetes mellitus (DM), hypertension and comorbidity among the adult population of Bangladesh.Study design This study analysed cross-sectional nationwide Bangladesh Demographic and Health Survey data from 2011. Comorbidity was defined as the coexistence of both DM and hypertension. Several socioeconomic and demographic factors such as age, sex, education, geographic location, administrative division, employment status, education and wealth index were considered as major explanatory variables. Inequality in prevalence and healthcare utilisation was measured using the ‘Lorenz curve’. Adjusted multiple logistic regression models were performed to observe the effects of different factors and reported as adjusted ORs (AORs) with 95% CIs. A p value of <0.05 was adopted as the level of statistical significance.Setting The study was conducted in Bangladesh.Participants A total of 7521 adult participants with availability of biomarkers information were included.Results The mean age of the study participants was 51.4 years (SD ±13.0). The prevalence of hypertension, diabetes and comorbidity were 29.7%, 11.0% and 4.5% respectively. Socioeconomic inequality was observed in the utilisation of healthcare services. A higher prevalence of hypertension and comorbidity was significantly associated with individuals aged >70 years (AOR 7.0, 95% CI 5.0 to 9.9; AOR 6.7, 95% CI 3.0 to 14.9). The risk of having hypertension, diabetes and comorbidity were significantly higher among more educated, unemployed as well as among individuals from Khulna division.Conclusions The study revealed a rising prevalence of hypertension, diabetes and comorbidity with inequality in service utilisation. A joint effort involving public, private and non-governmental organisations is necessary to ensure improved accessibility in service utilisation and to reduce the disease burden.